Analisis Kebijakan Jepang Bekerja Sama dengan Myanmar dalam Memenuhi Kepentingan Ekonomi Di Tahun 2011-2019 - Savitri, Putu Indah; Dharmiasih, D.A. Wiwik; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research aims to describe Japan’s attempts in accomplishing their economic interest through investation in Myanmar by using qualitative method. Japan encounters the declining human resource which causing labour shortage. This phenomenon leads Japan’s manufacturers to a major bankruptcy. Through Japan’s cooperation with Myanmar, Japan aims to expand their manufacturing companies in Myanmar in order to gain Myanmar’s labour force. However, there’s a large gap between the skill of Japan and Myanmar’s human resource. The researcher uses the concept of Foreign Policy and Infrastructure Investment as the framework. This research perceives that infrastructure investment impacting the skill of human resources and helps the expansion of Japan’s manufacturers in Myanmar. Keywords:Japan, Myanmar, Economy, Infrastructure Investment, Foreign Policy